Pertumbuhan Iman di Era Modern Menurut Markus 4 : 1 – 20 : Kunci dari Pemahaman , Refleksi , dan Dukungan Komunitas - Obehetan, Yeheskiel; Ruku, Noh; Nababan, Eva (Jurnal Arrabona, 2025)
This article discusses the parable of the sower taught by Jesus Christ in the Gospel of Mark 4:1-20 and its implications for faith growth in the modern era. The parable illustrates how the seed of God’s word is sown on different types of soil or human hearts, which affects its growth outcome. This study analyzes various types of soil: the path, rocky ground, thorns, and good soil, and how each type influences growth results. The article also explores the relevance of these changes in the contemporary context, focusing on modern challenges such as technological advancements, cultural shifts, and social factors that can impact individual spirituality. Additionally, the article offers practical approaches for implementing the teachings of the parable into daily life through the development of spiritual habits to support faith growth and strategies for overcoming obstacles in the modern world. In conclusion, the article emphasizes that although social contexts have changed, the principles of the parable of the sower remain relevant in helping individuals grow in strong and fruitful faith in today’s modern era.